(untitled) (Research, Society and Development, 2022)
To report the experiences of the resident in the multiprofessional visits carried out at the Burn Treatment Center (CTQ) in an Urgent and Emergency Hospital in the Metropolitan region of Belém, as well as contributions to Interprofessional Education. This is a descriptive study, of the experience report type, about experiences of the first year of residency, in 2021. The elaboration of this study was contemplated by the literature search phase to promote the description of the experiences and perception of the resident. The resident’s participation in the bedside visits at the CTQ made it possible to learn about the routine of the sector, collaborative practice, establishment of effective communication with the team. Thus, it is possible to obtain the preparation of specialists capable of acting with a focus on patient safety.